Penerapan Media Pembelajaran Game Edukatif bagi Anak Usia Dini TKQ Al-Banna (Neolectura, 2021)
Educational game applications are currently being used by students, from kindergarten to college students. Due to the idea of ??educators providing fun learning when learning is done online (on a network) with the Covid-19 virus outbreak, it requires every resident to practice social distancing where to avoid crowds, activities that require many participants and so on. Of course it is not an easy thing when students are